Tracing the Digital Path: Academic Information Systems in Indonesian Islamic Universities - Reza, Lukman (DJIT : Digital Journal of Information Technology, 2025)
Academic Information Systems (AIS) have become a foundational component in higher education, enabling institutions to manage student enrollment, academic records, course scheduling, and assessment processes efficiently. In the context of Indonesian Islamic higher education institutions (PTKIN), the development and adoption of AIS are influenced by unique cultural, technical, and institutional dynamics. This literature review explores the current state of AIS implementation in PTKIN, highlighting challenges and innovations based on a thematic synthesis of 12 peer-reviewed publications and a contextual case study of UIN Datokarama Palu.  The findings reveal five critical themes: (1) the functional scope of AIS modules tailored for dual religious and secular curricula, (2) infrastructure and technical limitations in PTKIN institutions, (3) human resource readiness and adaptability, (4) lack of interoperability with national systems such as PDDIKTI, and (5) emerging local innovations in AIS design and management. UIN Datokarama Palu’s experience with its internally developed AIS platform, ISEMA, illustrates the complexities and opportunities of homegrown systems in resource-constrained environments. While the platform has yet to be fully integrated with external databases, it demonstrates practical utility and institutional commitment to digital transformation. The review concludes that successful AIS implementation in PTKIN requires a balance between technological capabilities, organizational support, and user engagement. Recommendations include investing in scalable infrastructure, formalizing standard operating procedures (SOPs), enhancing user training, and pursuing national system integration. The experience of UIN Datokarama offers insights that are not only institution-specific but also applicable to similar educational contexts in Indonesia.